Bi-directional replication and random termination - Santamaría, D. (Oxford University Press, 2000)
Two-dimensional (2D) agarose gel electrophoresis was used to study termination of DNA replication in a shuttle vector, YRp7′, when it replicated in Escherichia coli, Saccharomyces cerevisiae and Xenopus egg extracts. In E.coli, the 2D gel patterns obtained were consistent with uni-directional replication initiated at a specific site, the ColE1 origin. In consequence, termination also occurred precisely at the ColE1 origin. In Xenopus egg extracts, the particular shape of the bubble arc as well as the triangular smear detected to the left of the simple-Y pattern indicated random initiation and termination. In S.cerevisiae, initiation occurred at the ARS1 origin and replication proceeded in a bi-directional manner. However, termination did not always occur at a specific site 180° across from the origin, but almost all along the south hemisphere of the plasmid. Inversion, deletion or replacement of DNA sequences located throughout this hemisphere did not eliminate random termination. Analysis of the replication intermediates of another yeast plasmid bearing a different origin, ARS305, also exhibited random termination. We propose that the random termination events observed in S.cerevisiae could be due to an asynchronous departure of both forks from the bi-directional origin in addition to differences in the rate of fork progression. These observations could be extended to all bi-directional origins.